Using muscle homing peptide CyPep10 to deliver phosphorodiamidate morpholino oligomers in the mdx mouse - Schneider, Anne-Fleur E.; Tanganyika-de Winter, Christa L.; Jirka, Silvana M.G.; Tan, Xuyu; Thompson, Emily G.; Ha, Kristen; Mitra, Anindita; Garcia, Stephanie; Luimes, Marleen; Oliver, Ryan A.; Guerlavais, Vincent; Aartsma-Rus, Annemieke (Molecular therapy. Nucleic acids, 2025)
The severe muscle wasting disorder Duchenne muscular dystrophy (DMD) is characterized by the absence of dystrophin, a protein that is essential for muscle stability. Restoring this protein has therapeutic potential. Antisense oligonucleotides (ASOs), designed to target and skip exons, can restore the reading frame that is disrupted in these patients, enabling the production of partially functional dystrophin. Achieving optimal dystrophin restoration remains challenging due to limited delivery and cellular uptake. Muscle homing peptides conjugated to ASOs are a way to achieve this. Previously, CyPep10 (CP10) has been used to significantly increase exon skipping efficiency for the 2′-O-methyl phosphorothioate chemistry in the mdx mouse model for DMD. Here, we explore the effect of using peptide CP10 as a conjugate to phosphorodiamidate morpholino oligomers (PMOs) ASOs to improve muscle delivery, thereby hoping to achieve increased treatment efficiency. Overall, we confirmed the homing ability of CP10 and observed significantly increased muscle tissue concentration levels of PMO when CP10 was conjugated. This did not lead to increased levels of exon skipping or dystrophin restoration. Conjugating both a cell-penetrating peptide (CPP) and CP10 to a PMO showed that increased exon skipping efficiency can be achieved to a slightly greater extent than with CPP-PMO treatment. [Display omitted] This study by Schneider and colleagues found that conjugation of muscle homing peptide CyPep10 to a phosphorodiamidate morpholino oligomer (PMO) increased muscle tissue concentration of PMOs and that double conjugation with a cell-penetrating peptide with CyPep10 improved exon skipping efficiency as well as muscle pathology hallmarks.